2020
DOI: 10.1108/ajar-05-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate governance on intellectual capital efficiency: evidence from Islamic banks of OIC countries

Abstract: PurposeThe purpose of this study is to examine the impact of corporate governance (CG) on intellectual capital efficiency (ICE) in Islamic banks (IBs) of Organisation of Islamic Cooperation (OIC) countries.Design/methodology/approachA sample of 129 IBs is drawn from the 29 OIC countries from 2008 to 2017. A two-step system of the generalised method of moments has been employed to account for the unobserved endogeneity and heteroscedasticity issue that arose due to time-variant and time-invariant variables.Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 59 publications
(92 reference statements)
3
33
1
3
Order By: Relevance
“…For each regression, the diagnostic test satisfies the condition that instruments are uncorrelated and that the error terms are different across models. In addition, the AR ( 1) and ( 2) test results show absence of autocorrelation problems across models, as suggested by the literature (Nomran and Haron, 2020;Aslam and Haron, 2020b). The lag values of LAS, LTD, and NPLR are positive and statistically significant in all models, indicating that the past year's LAS, LTD, and NPLR values significantly enhance the current year's LAS, LTD, and NPLR values of Islamic banks.…”
supporting
confidence: 77%
See 4 more Smart Citations
“…For each regression, the diagnostic test satisfies the condition that instruments are uncorrelated and that the error terms are different across models. In addition, the AR ( 1) and ( 2) test results show absence of autocorrelation problems across models, as suggested by the literature (Nomran and Haron, 2020;Aslam and Haron, 2020b). The lag values of LAS, LTD, and NPLR are positive and statistically significant in all models, indicating that the past year's LAS, LTD, and NPLR values significantly enhance the current year's LAS, LTD, and NPLR values of Islamic banks.…”
supporting
confidence: 77%
“…A high proportion of outside directors could, thus, weaken the performance of the advisory tasks in the organization (Aslam, and Haron, 2020b). Tarchouna et al (2017) additionally found a noteworthy negative connection between board independence and non-performing loans.…”
Section: B2 Board Independencementioning
confidence: 97%
See 3 more Smart Citations